Desain Topologi Jaringan (FTTR) Berbasis (GPON) dengan Pendekatan Algoritma Dijkstra di SMK NU Ma'arif Kudus - Rizky Alhusani Gifari; Nur Aeni Widiastuti; Gentur Wahyu Nyipto Wibowo (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The need for reliable internet connectivity in educational environments is crucial, but is often hampered by inefficient network infrastructure. This study aims to design an optimal Fiber To The Room (FTTR) network topology design based on Gigabit Passive Optical Network (GPON) at SMK NU Ma'arif Kudus, focusing on the efficiency of fiber optic cable installation routes. The research method used is engineering design with a quantitative approach, where the school architectural plan is modeled into a weighted graph. Route optimization is carried out by implementing the Dijkstra Algorithm to find the shortest path from the center node (ODC) to all node termination points (ODP). While node I (ODC) is designated as the starting node because it functions as the network distribution center. The calculation process is carried out by determining the minimum distance from the starting node to all destination nodes (ODP). The calculation results show that the shortest path is divided into two main routes, namely I to C to B to A to D to E and I to F to G to H. The selection of this node is proven to be able to produce a more efficient total distance compared to direct paths in several network segments. Based on these results, it can be concluded that Dijkstra's algorithm is effective in fiber optic network planning because it can optimally determine the path with the minimum distance. The application of this method is expected to assist in decision-making regarding fiber optic network infrastructure planning, making it more efficient and applicable for implementation in school environments.